EFFECTS OF LEADERSHIP STRATEGY ON PERFORMANCE OF GOVERNMENT SECURITY AGENCY (A CASE OF NATIONAL POLICE SERVICE COMMISSION OF KENYA) - Aludo, David Onyango; Mburu, Dr. David Kiarie (IJRDO - Journal of Applied Management Science, 2016)
The purpose of this study was to establish the effects of leadership strategy on performanceof government security agency and targeted the National Police Service Commission ofKenya as an area of study. Specifically, the study explores the effects of democraticleadership, transformational leadership, transactional leadership and authoritarianleadership on performance of the National Police Service Commission. The effects ofleadership strategy and performance of government security agency has been the area ofconcern and there was need to explore the gaps, which exist between the two areas. Thestudy reviews related literature, which supported the study gaps and necessitated the needfor this study. This study used a descriptive research based on the perceptions of seniormanagers and the operational members of staff, who were used as the respondents of thisstudy. A structured self-completed research questionnaire was administered by hand andcollected after a period of two weeks. The component of analysis for this study was 150employees, which formed the target population for this study. A stratified samplingtechnique was employed on various categories where 30% of the target population wasselected to form the sample size of this study. The response rate of 93.3% from therespondents made it easier for the study to be carried out. Data collected was presentedand analyzed using both descriptive and inferential statistics. The statistical package forsocial science was used to facilitate the data analysis. The study used correlation statisticalanalysis techniques to aid in establishing the relationship between independent variablesand dependent variable. Analysis of variance, means, standard deviation, percentages,graphs and regression model were, used to ease the study findings and discussions. Fromthe study findings, the statistics showed that there was a correlation of democraticleadership and performance with a correlation figure of 0.047, transformation leadershipand performance with a correlation figure of 0.089, transactional leadership andperformance with a correlation figure of 0.023 and authoritarian leadership andperformance with a correlation figure of 0.103. The conclusion of this study showed thatthe use of democratic leadership and transformational leadership was not fully embracedwithin the organization, transactional leadership was disputed by the respondents whoindicated that its use in the organization may cause high staff turnover and thatauthoritarian leadership affects efficiency and effective performance negatively. From theconclusions of the study, the study recommended that the organization should embracedemocratic leadership but more emphasis should be given transformation leadership. Careshould be taken when transactional leadership is to be practiced since it has its short fallsand authoritarian should be used as the last resort and needs to be discouraged ifefficiency and effective performance is to be realized within the organization.